Validation of the Norwegian version of the 10-item version of Clinical Outcomes in Routine Evaluations Outcome Measure (CORE-10) in a Norwegian adolescent population (aged 14-18). - Solem, Kenth Moland; Moen, Connie Malen (UiT Norges arktiske universitet, 2015)
Background: This study examined whether the 10 item version of Clinical Outcomes in Routine Evaluations Outcome Measure (CORE-10) can be used in the Norwegian adolescent population aged 14 to 18 years. The target population was 531 adolescents attending junior and senior high school, 56 adolescent outpatients from Division of Child and Adolescent Mental Health (DCAMH), and 182 adolescents utilizing a counseling service in Tromsø. Method: Readability for both Clinical Outcomes in Routine Evaluations Outcome Measure (CORE-OM) and CORE-10 was calculated using the Flesch-Kincaid Formula. Further the internal consistency and a clinical cut-off score were calculated, and the effect of age and gender on summed up CORE-10 and CORE-OM scores was examined. A Fit Confirmatory Factor Analysis (FCFA) was also conducted on the CORE-OM scores from the non-clinical sample. Results: The readability level for CORE-10 and CORE-OM was suitable for adolescents with a reading level from hence 6th and 7th grade. The internal consistency of CORE-10 was good, and the results suggest a cut-off score of 1.4 for CORE-10. In all samples, a significant gender difference was observed; with females scoring higher than males. A Fit Confirmatory Factor Analysis (FCFA) indicated that the data from the non-clinical sample fit an underlying four-factor structure. Conclusion: When applying CORE-10 to a Norwegian adolescence population, results from the present study suggest that CORE-10 can be used in the Norwegian adolescent population. Furthermore, the cut-off score for CORE-10 is different from the cut-off score for adults, and we recommend the cut-off score to be adjusted according to the adolescent population. Keywords: Outcome measures, CORE-10, CORE-OM, validation, adolescents